RESULTS OF EVALUATING THE EFFICACY OF SECUKINUMAB VERSUS ADALIMUMAB IN TREATING PSORIATIC ARTHRITIS BY USING THE MATCHING-ADJUSTED INDIRECT COMPARISON METHOD - T. V. Korotaeva (Современная ревматология)
To date there have been no results of a direct comparison of the efficiency of using tumor necrosis factor-α inhibitors, secukinumab (SCM) and adalimumab (ADA) in particular, to treat psoriatic arthritis (PsA). This suggests that there is a need to apply the Matching-Adjusted Indirect Comparison (MAIC) method that will be able to choose a treatment option for PsA. Objective: to compare the efficacy of SCM andADAby using the MAIC method in patients with active PsA.Patients and methods. The results of usingADAin the Adalimumab Effectiveness in Psoriatic Trial (ADEPT), a randomized clinical trial (RCT), and SCM in the FUTURE 2 RCT were compared according to theAmericanCollegeof Rheumatology (ACR) and Psoriatic Area and Severity Index (PASI) criteria. The analysis based on the MAIC principles included aggregated data on 151 patients with active PsA from the ADEPT RCT and 189 patients from the FUTURE 2 RCT.Results. At 16 weeks, ACR20/50/70 responses were observed in 74.4/50.1/18.5% of the patients treated with SCM 150 mg, in 65.5/50.1/50.1% of those treated with SCM 300 mg, and in 55.6/32.5/20.5% of those receivingADA, respectively. Both doses of SCM had a significant advantage over the dose ofADAaccording to ACR20 and ACR50 responses. A PASI75 response forADAand SCM 150/300 mg was observed in 60.9 and 59.5/64.1% of the patients; and a PASI90 response was seen in 39.1 and 47.7/40.8% of the patients, respectively. At 24 weeks of treatment, ACR20, ACR50, and HAQ-DI responses in patients receiving SCM 150 and 300 mg were significantly higher than in PsA patients takingADA. No statistically significant differences were observed in ACR70 response rates. The ratio of ACR20 and ACR50 indicators was similar after 48 weeks of treatment initiation. Assessment of the dynamics of psoriasis yielded similar results.Conclusion. Patients with active PsA demonstrated the advantage of therapy with SCM 150 and 300 mg over that withADA. There was a greater improvement in quality of life in patients with PSA treated with SCM.